2013
DOI: 10.1371/journal.pone.0074836
|View full text |Cite
|
Sign up to set email alerts
|

Public Views on Food Addiction and Obesity: Implications for Policy and Treatment

Abstract: BackgroundAccording to their advocates, neurobiological explanations of overeating, or “food addiction”, have the potential to impact public understanding and treatment of obesity. In this study, we examine the public’s acceptance of the concept of food addiction as an explanation of overeating and assess its effects upon their attitudes toward obese persons and the treatment of obesity.Methods and FindingsWe conducted an online survey of 479 adults from the US (n = 215) and Australia (n = 264). There was subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 29 publications
3
38
1
Order By: Relevance
“…This interpretation is in line with the findings of a recent study investigating the US and Australian public's opinion on food addiction. This survey revealed that most respondents consider compulsive eating as a matter of choice and individual responsibility, while other etiologic factors such as genetics or environmental influences were seen as less relevant to food addiction (Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…This interpretation is in line with the findings of a recent study investigating the US and Australian public's opinion on food addiction. This survey revealed that most respondents consider compulsive eating as a matter of choice and individual responsibility, while other etiologic factors such as genetics or environmental influences were seen as less relevant to food addiction (Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…The notion of 'food addiction' has gained widespread media attention and public support for its existence appears to be strong (Barry, Brescoll, Brownell, & Schlesinger, 2009;Bird, Murphy, Bake, Albayrak, & Mercer, 2013;Lee et al, 2013;Wilson et al, 2009). In one study, 86% of Australians and Americans endorsed the idea that some foods have addictive properties and 72% believed that food addiction could account for some cases of obesity (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 86% of Australians and Americans endorsed the idea that some foods have addictive properties and 72% believed that food addiction could account for some cases of obesity (Lee et al, 2013). More recently, it has been shown that a substantial proportion (42%e52%) of people from community samples perceive themselves to be addicted to food (Hardman et al, 2015;Meadows & Higgs, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Yet both obesity and addiction still carry stigma today in western societies, raising the risk that their combination might again prove reinforcing. Recent data present an ambiguous picture about whether acceptance of obesity as an addictive condition makes any difference to social attitudes about overweight and obese people, or about the policy measures perceived as appropriate [8,80]. Certainly it cannot be ruled out that attribution of addiction (as a chronic brain disease) will hurt more than it helps, just as did attribution of addiction (as psychic disorder) in the 1950s [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the stigmatizing attribution of addiction to people already stigmatized as obese may amplify the social harms that they suffer. Empirically, as well as logically, recent survey evidence shows that the neurochemical concept of obesity, as with drug addiction and eating disorders, can coexist with attribution of personal responsibility for the condition, and thus with blaming the impaired, addicted consumer rather than the supplier [7][8][9]. Furthermore, irrespective of any impact on stigma, attention to the neurophysiological basis of addictive conditions focuses policy action on individual medical intervention rather than more cost-effective population measures [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%